2019
DOI: 10.1093/jhps/hnz019
|View full text |Cite
|
Sign up to set email alerts
|

Increased pelvic mobility and altered hip muscles contraction patterns: two-year follow-up cam-FAIS corrective surgery

Abstract: Femoroacetabular impingement syndrome (FAIS) surgery can produce improvements in function and patient satisfaction; however, data on muscle assessment and kinematics of high mobility tasks of post-operative patients is limited. The purpose of this study was to evaluate kinematics and muscle activity during a deep squat task, as well as muscle strength in a 2-year follow-up FAIS corrective surgery. Eleven cam morphology patients underwent motion and electromyography capture while performing a squat task prior a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 61 publications
0
9
0
Order By: Relevance
“…A plan can also be developed to help the patient prepare both mentally and physically for surgery [ 21 ]. A pre-operative assessment of ROM, strength, general function, pain level and quality of life can be compared to post-operative assessments as well as the benefits of surgical invention and ultimately improve patient care [ 22 ]. Grant et al .…”
Section: Discussionmentioning
confidence: 99%
“…A plan can also be developed to help the patient prepare both mentally and physically for surgery [ 21 ]. A pre-operative assessment of ROM, strength, general function, pain level and quality of life can be compared to post-operative assessments as well as the benefits of surgical invention and ultimately improve patient care [ 22 ]. Grant et al .…”
Section: Discussionmentioning
confidence: 99%
“…The bi-articular semimembranosus acts to overcome the bodyweight load and extend the hip. Increased activation of the other synergist medial hamstring, the semitendinosus, was already explored postoperatively during squat descent 36 . However, the postoperative increase of the semimembranosus force only reached significance in the ascending phase of the squat, as perhaps during the descending phase, the static optimization approach may not have perfectly expressed the eccentric mechanisms that were altered by the joint pathology.…”
Section: Discussionmentioning
confidence: 99%
“…This study used a subset of participants enrolled in other studies 36,38 , and the main surgical findings are reported in Beaulé et al (2017) 6 . The study was approved by the hospital's and university's research ethics boards and all participants provided written informed consent for participation.…”
Section: Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…The cam-type hip morphology is defined by an aspherical femoral head-neck that produces elevated alpha angles and decreased anterior head-neck offsets (Nötzli et al, 2002), and can result in anterior hip or groin pain, labral tears, and damage to the acetabular articular cartilage (Ito et al, 2001;Gosvig et al, 2008;Bowman et al, 2010;Speirs et al, 2013). Previous studies on FAI pathomechanism have speculated the existence of the cam-type morphology as causative to limit the functional range of motion (ROM), which has been shown in patients with cam-type FAI who demonstrated less hip and pelvic ROM during gait (Kennedy et al, 2009;Rylander et al, 2011;Brisson et al, 2013;Diamond et al, 2016;Ng et al, 2018b;Catelli et al, 2019b;Savage et al, 2021), deep squat (Lamontagne et al, 2009(Lamontagne et al, , 2011Ng et al, 2015;Bagwell et al, 2016;Catelli et al, 2019aCatelli et al, , 2020, stairs (Rylander et al, 2013;Diamond et al, 2018;Catelli et al, 2019aCatelli et al, , 2021, and clinical assessments (Kapron et al, 2012;Ng et al, 2016). Recent in silico analyses have demonstrated reduced hip contact forces (HCFs) compared to matched healthy individuals while performing different tasks (Catelli et al, 2019b(Catelli et al, , 2020(Catelli et al, , 2021.…”
Section: Introductionmentioning
confidence: 99%